2014
DOI: 10.1002/ajim.22338
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in California farm workers, 1988–2010

Abstract: These farm workers experience proportionally more prostate, kidney and renal pelvis, brain, liver, stomach, cervix and leukemia and less breast, melanoma, and colorectal cancer than reference populations. For many sites, cancer is not diagnosed as early in the farm workers as in the comparison groups, except for colorectal cancer in females and melanoma in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…Compared to population counterparts, risk of later stage prostate, breast or colorectal cancer diagnosis was not found in Californian Hispanic farmworkers; nor for colorectal cancer stage in French farm men and women. 14,16 Findings in our study were similar to these cohorts for women, although slightly different for men. However, compared to our study, the French and Californian cohorts were younger and defined by occupation not residence.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Compared to population counterparts, risk of later stage prostate, breast or colorectal cancer diagnosis was not found in Californian Hispanic farmworkers; nor for colorectal cancer stage in French farm men and women. 14,16 Findings in our study were similar to these cohorts for women, although slightly different for men. However, compared to our study, the French and Californian cohorts were younger and defined by occupation not residence.…”
Section: Discussionsupporting
confidence: 84%
“…11,12 International studies have generally reported reduced cancer risk in farmers compared with others for breast and colorectal cancers, with mixed results for prostate cancer. [13][14][15] Stage at diagnosis has only been reported in two cohorts involving farmers in the international literature. 14,16 This study will examine if stage at diagnosis differs between farm, rural non-farm and urban residents for prostate, breast and colorectal cancers in the 45 and Up cohort.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study among Mexican Latinos in Texas identified associations between exposure to agrichemicals, being US-born, lack of physical activity and PC family history and higher risk of PC [ 54 ]. This finding is supported by the observation that California farm workers, which are predominantly Mexican migrant workers, showed disproportionately more PC cases than Californian NHW [ 55 ]. Diets high in red meat have been proposed to increase PC risk, and an association between red meat cooked at high temperatures and risk was reported among Latinos in a multi-ethnic study [ 56 ].…”
Section: Prostate Cancermentioning
confidence: 57%
“…Similarly, an analysis on members of the United Farm Workers of America in California from 1973 – 2000 found farmers to be at reduced risk for lung cancer [37]. In a study assessing cancer risk in California farm workers from 1988 – 2010, less lung cancer was found in farm workers compared to a non-Hispanic white population assessed [38]. On the other hand, a study comparing farmers to non-farmers in the Province of Vercelli in Italy, farmers had increased risk of numerous cancers including lung cancer (OR = 1.59), with males having a higher lung cancer risk than females [39] The AGRICAN cohort study from France summarizing data collected from 2005 – 2009 reported no significant changes in lung cancer risk for farm owners and agriculture workers [40].…”
Section: Lung Cancermentioning
confidence: 99%